THE INFLUENCE OF PSYCHOLOGICAL CAPITAL ON JOB PERFORMANCE AMONG SALESPEOPLE AT PT SI - Karlina; Citrawanti Oktavia (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
The growth of the trading and distributor industry in Indonesia has created a highly competitive climate, requiring salespersons to demonstrate adaptive and innovative performance. This study aims to examine the influence of Psychological Capital (PsyCap) on the Job Performance of salespersons at PT SI, an industrial equipment distributor in Cikarang currently facing challenges related to declining performance and fluctuating sales targets. The research design employs a quantitative approach utilizing a census method (saturated sampling), involving 31 salespersons as respondents due to the relatively small population size. The research instruments employed were the Psychological Capital Questionnaire (PCQ) to measure the dimensions of hope, self-efficacy, resilience, and optimism, and the Individual Work Performance Framework (IWPQ) to assess task performance, contextual performance, and counterproductive work behavior. Data analysis was conducted using simple linear regression to predict the influence of the independent variable on the dependent variable. This study is expected to provide empirical insights into the importance of employees' internal psychological aspects in sustaining performance amidst the pressures of the Business to Business (B2B) industry, and serves as a foundation for management to design HR capacity-building strategies that do not rely solely on financial incentives.